The Delayed-steroid-strategy (dss) For Idiopathic Granulomatous Mastitis During The Covid-19 Pandemic. A Case Series. - Mohamad Farhan MY; Norlia A (MEDICINE AND HEALTH, UNIVERSITI KEBANGSAAN MALAYSIA, 2024)
Medicine & Health, Volume 18 Issue 2 Page (630–636)